Application of A Physiological Strain Index in Evaluating Responses to Exercise Stress – A Comparison Between Endurance and High Intensity Intermittent Trained Athletes - Pokora, Ilona (J Hum Kinet, 2016)
The study evaluated differences in response to exercise stress between endurance and high-intensity intermittent trained athletes in a thermoneutral environment using a physiological strain index (PSI). Thirty-two subjects participated in a running exercise under normal (23°C, 50% RH) conditions. The group included nine endurance trained athletes (middle-distance runners - MD), twelve high-intensity intermittent trained athletes (soccer players - HIIT) and eleven students who constituted a control group. The exercise started at a speed of 4 km·h(–1) which was increased every 3 min by 2 km·h(–1) to volitional exhaustion. The heart rate was recorded with a heart rate monitor and aural canal temperature was measured using an aural canal temperature probe. The physiological strain index (PSI) and the contribution of the circulatory and thermal components to the overall physiological strain were calculated from the heart rate and aural canal temperature. The physiological strain index differed between the study and control participants, but not between the MD and HIIT groups. The physiological strain in response to exercise stress in a thermoneutral environment was mainly determined based on the circulatory strain (MD group - 73%, HIIT group – 70%). The contribution of the circulatory and thermal components to the physiological strain did not differ significantly between the trained groups (MD and HIIT) despite important differences in morphological characteristics and training-induced systemic cardiovascular and thermoregulatory adaptations.